How far are groundwater resource assessments in India reliable?. Issue 1 (6th March 2023) - Vaishnavi, P.N.A.; Kumar, M. Dinesh
Abstract: The article critically reviews the methodology adopted by the Central Ground Water Board (CGWB) for the assessment of groundwater resources in India. The authors developed a water balance equation that simulates the changes in annual and seasonal groundwater storages of an agricultural region, using a water accounting framework; they solved the developed equation using the data of annual and seasonal water level fluctuations for a wet year for Ludhiana district of Punjab to estimate different components of the water balance. The estimated values are used to test the robustness of the CGWB methodology for monsoon recharge. The annual groundwater storage change obtained from solving the water balance equation was compared with the observed change in annual groundwater storage and was found to closely tally. As per the water balance equation, the CGWB estimates of rainfall recharge conform to the annual water level fluctuations recorded by the agency and therefore are not reliable. Hence, we could infer that our methodology is superior to that of CGWB for estimating monsoon recharge. The validated equation was also used to estimate the recharge from rainfall during a dry year. Using these outputs in a simple groundwater balance equation, irrigation return flows were estimated for the wet and dry years. The equation was then extended to the Ahmednagar district of Maharashtra, a hard rock area, for estimating the surface water import during a wet year, the key unknown in the region's water balance. Hence, our methodology can be employed to estimate rainfall recharge for dry years using annual changes in groundwater storage and estimated consumptive uses of water, when the "WLF approach, " used by CGWB, fails, owing to the presence of an additional variable, that is, monsoon draft. For wet years, it can be used to arrive at the consumptive use of water for various purposes.